2015
DOI: 10.1099/vir.0.000066
|View full text |Cite
|
Sign up to set email alerts
|

Diverse roles and interactions of RNA structures during the replication of positive-stranded RNA viruses of humans and animals

Abstract: Positive-stranded RNA viruses include important human, animal and plant pathogens. Their genomes are able to fold into complex structures stabilized by base pairing between individual nucleotides, many of which are highly conserved and have essential functions during virus replication. With new studies and technological advances the diversity of roles, mechanisms and interactions in which such structured viral RNA functions is becoming increasingly clear. It is also evident that many RNA structures do not func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…The molecular basis for these data is unclear, but the defects in the mutants might already occur at the RNA level, causing the RNA to adopt an unfavorable structure for translation and/or replication (44,45). Alternatively, the extensive sequence divergence of prM TMDs-which is much higher than that of E TMDs (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…The molecular basis for these data is unclear, but the defects in the mutants might already occur at the RNA level, causing the RNA to adopt an unfavorable structure for translation and/or replication (44,45). Alternatively, the extensive sequence divergence of prM TMDs-which is much higher than that of E TMDs (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, the folded architecture of the SARS-CoV-2 genome may enable it to hide in plain sight, reducing activation of host pattern recognition receptors (Bowie and Unterholzner 2008). In other well-structured positive-stranded RNA viruses like HCV and MNV, the formation of genome-scale ordered RNA structure (GORS) correlates with decreased activation of antiviral pathways (McFadden et al 2013;Tuplin 2015). Cell-based assays have shown that highly structured viral transcripts have a reduced propensity to activate interferon responses when compared with less structured viral RNAs (Witteveldt et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…RNA secondary structures perform a wide range of important biological functions in addition to their central roles in ribosomes and tRNAs. Auxiliary structural functions include regulating gene expression levels in mammalian cells (2), constraining mutations during bacterial evolution (7), controlling temperature sensitivity (3, 12, 36) and viral replication (1, 34, 35), regulating folding and post-translational modification of encoded proteins (14, 15).…”
Section: Introductionmentioning
confidence: 99%